Managerial and Cultural Challenges Resulting from the Monitoring of Psychophysiological Parameters of a Human Being - Marcin BERLIK; Bartosz KIRCHNER (Communications of International Proceedings, 2021)
The purpose of this article is to indicate the challenges the organization must face with when implementing the monitoring of human psychophysiological parameters and applying new technologies in Industry 4.0. According to the authors, this study also includes the important socio-cultural context, which requires particular recognition of the employee, especially in the case of obtaining the sensitive data of such a person. Moreover, this article includes the description of Industry 4.0 and monitoring of the psychophysiological parameters of an employee, from the technical point of view. The desire to exceed human capabilities is also presented, according to the description in cultural sciences in the scope of transhumanism, which is currently implemented during the Industrial Revolution 4.0. Cultural challenges related to the monitoring of psychophysiological parameters are also presented, as well as areas of particular attention of managers, if they want to effectively implement this type of labour observation in their organizations.
Keywords: Industry 4.0; monitoring the psychophysiological parameters; human factor; management; cultural aspects; transhumanism; ergonomics; safety